Improving Protein Crystal Quality by the Without-Oil Microbatch Method: Crystallization and Preliminary X-ray Diffraction Analysis of Glutathione Synthetase from Pseudoalteromonas haloplanktis - Antonello Merlino; Irene Russo Krauss; Antonella Albino; Andrea Pica; Alessandro Vergara; Mariorosario Masullo; Emmanuele De Vendittis; Filomena Sica (International Journal of Molecular Sciences, 2011)
Glutathione synthetases catalyze the ATP-dependent synthesis of glutathione from L-γ-glutamyl-L-cysteine and glycine. Although these enzymes have been sequenced and characterized from a variety of biological sources, their exact catalytic mechanism is not fully understood and nothing is known about their adaptation at extremophilic environments. Glutathione synthetase from the Antarctic eubacterium Pseudoalteromonas haloplanktis (PhGshB) has been expressed, purified and successfully crystallized. An overall improvement of the crystal quality has been obtained by adapting the crystal growth conditions found with vapor diffusion experiments to the without-oil microbatch method. The best crystals of PhGshB diffract to 2.34 Å resolution and belong to space group P212121, with unit-cell parameters a = 83.28 Å, b = 119.88 Å, c = 159.82 Å. Refinement of the model, obtained using phases derived from the structure of the same enzyme from Escherichia coli by molecular replacement, is in progress. The structural determination will provide the first structural characterization of a psychrophilic glutathione synthetase reported to date.